Tracking visual attention during learning of complex science concepts with augmented 3D visualizations - Yang, Fang-Ying; Wang, Hui-Yun (Computers and education, 2023)
The main purpose of the study was to explore how different augmented 3D visualizations may affect the learning of complex science concepts using the eye tracking method. An Augmented Reality (AR) learning system incorporated with different 3D visualizations was developed to assist conceptual learning in the topic of “molecular shapes.” Learners' visual attention during the AR learning was recorded using a mobile eye tracking system. Participants were 32 10th grade students. Pre- and post-tests were used to assess students' learning achievements. Learners were grouped into low and high achievers according to the posttest result. To analyze the associations between learners' visual attentions and learning achievements, correlation, t-test, correlation, and regression analyses were applied. Additionally, we conducted lag sequential analysis (LSA) to compare the visual transitions of different groups of achievers. The results showed that learners’ conceptual understanding was improved after the AR learning activity. Among the different 3D visualizations, learners attended more to the static and dynamic types in the basic learning stage and to the static and interactive types in the advanced learning stage. Attention to the 3D static model was found to associate more to the attention to the interactive type. The correlation and regression analyses found that the cognitive effort to integrate information about the static 3D model was the key predictor for the learning achievement. LSA showed that high achievers displayed a higher chance of looking back to the static 3D model from other AOIs. The visual pattern analysis suggested that a guidance to connect information delivered by the static and the animated visual representations is necessary for complex conceptual learning. •Visual attention to the augmented 3D static objects predicted learning achievement.•Visual attentions to the 3D static and interactive models were highly correlated.•Low achievers attended more to the interactive 3D objects.•High achievers looked back to the static 3D object from other AOIs more frequently.•High achievers made more sequential transitions between text and 3D objects.